(E)-2-Cyano-3-(substituted phenyl)acrylamide analogs as potent inhibitors of tyrosinase: A linear β-phenyl-α, β-unsaturated carbonyl scaffold. Issue 24 (15th December 2015) - Son, Sujin; Kim, Haewon; Yun, Hwi Young; Kim, Do Hyun; Ullah, Sultan; Kim, Seong Jin; Kim, Yeon-Jeong; Kim, Min-Soo; Yoo, Jin-Wook; Chun, Pusoon; Moon, Hyung Ryong
Graphical abstract: Abstract: In this study, we synthesized ( E )-2-cyano-3-(substituted phenyl)acrylamide (CPA ) derivatives which possess a linear β-phenyl-α, β-unsaturated carbonyl scaffold and examined their inhibitory activities against tyrosinase.CPA analogs exerted inhibitory activity against mushroom tyrosinase. Results from the docking simulation indicated thatCPA2 could bind directly to the active site of mushroom tyrosinase and the binding affinity ofCPA2 for tyrosinase might be higher than that of kojic acid, a well-known potent tyrosinase inhibitor. In B16F10 cells, CPA2 significantly suppressed tyrosinase activity and melanogenesis in a dose-dependent manner. At the concentration of 25 μM, CPA2 exhibited tyrosinase inhibitory activity comparable to that of kojic acid with no cytotoxic effect. Results from the present study suggest thatCPA2 bearing a linear β-phenyl-α, β-unsaturated carbonyl scaffold may be the potential candidate for treatment of diseases associated with hyperpigmentation and that a linear β-phenyl-α, β-unsaturated carbonyl scaffold might be closely related to potent tyrosinase inhibition.